REKONDISI MESIN BUBUT DO ALL LT.13 DI LABORATORIUM MEKANIK POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Fadzila Septia; Delfiana Octora; Hasdiansah Hasdiansah; Pristiansyah Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Maintenance on production machines plays an important role in the smooth running of the production process, so the time interval for the replacement of components and machine maintenance must be properly scheduled. The implementation method applied is the 5 why observation method to solve problems that arise from the results of initial data collection which is then followed by a process of planning improvements and corrective actions. This paper aims to discuss the action of restoring the condition (reconditioning) of the Do All Lt. 13 lathe which focuses on the problem: the cooling system (colling system), the braking system (brake system), and geometric testing. From the results of the function test, the damage to the brake system and coolant system returned to function. For 13 geometric tests there are some deviations that occur in the machine.